15/121 would be the probability. I am not sure if it can simplify any more! :)
Given: Number of red marbles = 2
Number of white marbles = 5
Number of blue marbles = 3
Total marbles =2+5+3=10
If we choose first marble from the bag, then the probability of having red marbles will be :-
If we choose second marble after replacement (total remains same) from the bag, then the prob ability of having blue marbles will be :-
Since, both the events are independent.
Therefore, the probability of choosing red marble then blue marble is given by :-
15/121 is the answer.
15/121 is the sum
Probability of picking a red = number of reds in the bag / total number of marbles in the bag
= 3 / (3 + 3 + 5)
Probability of picking a blue = 5/11.
These 2 events are independent so we multiply probabilities, therefore the
Probability of (a red then a blue) = 3/11 * 5 /11
total-11P(red)= 3/11P(blue)=5/11P(red+blue)= 3/11*5/11= 15/121
P(red and blue) = 0.1667
Let A represent choosing a red marble, there are 3 red marbles
Let B represent choosing a blue marble, there are 4 blue marbles
There are 12 total marbles
P(A) = 3/12
P(B) = 4/12
choosing the first one, then replacing means the first choice has no effect on the probabilities of the second choice, so the situation is independent.
When calculating the probability of independent events, you multiply the probabilities together. There are 2 scenarios where we can get a red and blue marble..
Choosing a red, then a blue marble, the probability is
(3/12)( 4/12) = 12/144 = 1/12
Choosing a blue, then a red marble, the probability is
(4/12)(3/12) = 12/144 = 1/12
So we have a
(1/12) + (1/12) = 2/12 = 1/6 chance for that to happen, to
P(A and B) = 1/6 = 0.1667
i think something is missing in your question because y-1=(x-12) would not pass through the point (-4,-3). because if you replace x by -4 your are supposed to find y=-3 which is not the case her. if you replace x by -4 you find =-15.
i assume the right equation is y-1=1/4*(x-12) because this one is passing through both your points (if you are interested to know how i found that out i can tell you).
in this equation if i replace x by -4 i find y=-3 and if i replace x by 12, i find y=1 so the line representing this equation is passing through those 2 points.
then the standard form of the equation is finding an expression of y in function of x
hope that .
do you confirm there was a mistake in the question?